Optimization of pullulanase activity through design of experiment (DOE) - Norsalita, Abd Talib (2010)
Enzyme has been used widely in industries today due to its capability in catalyzing various types of biochemical reactions. However, the high cost of enzyme gives problems to the enzyme industries. A research was done to optimize the pullulanase activity from Bacillus Acidopullulyticus using experimental design. Two level Full Factorial design was applied in the screening process of four parameters for pullulanase activity and only three parameters were recognized as significant and effective factors for pullulanase activity. The three significant parameters were pH, enzyme and substrate concentration. Thus the three parameters were selected for further optimization studies using response surface methodology (RSM) in Design Expert version 7.1.6 software with Central Composite Design (CCD) mode. Thirty four sets of experiments with different parameter values were suggested. The predicted optimum values with R2 of 0.8729 for pH, enzyme concentration, substrate concentration and pullulanase activity were 6.60, 11.11 U/ml, 4.44% (w/v) and 3.17 U/ml respectively. One validation experiment was run using the optimized parameter and resulted 3.05 U/ml pullulanase activities as compared to the suggested values of 3.17 U/ml. As a conclusion, this research was successful to increase the pullulanase activity with a minimum numbers of experiments.